Availability of electroconvulsive therapy in public health services in the last decade in brazil - Mazucco, Júlia Pellizon (2024)
Objective To identify the current treatment options for electroconvulsive therapy (ECT) therapy in public services linked to the Unified Health System in Brazil and compare them with data published in 2012 based on their availability. Methods In this retrospective observational study, we mapped institutions that perform ECT under public health services in Brazil. A questionnaire was administered to active and inactive service centers between August 2022 and June 2023. Results We identified 16 institutions that performed ECT, including 12 linked to public universities and 4 with various links. In the last decade, 2 new public services that perform ECT in the country have emerged, whereas 4 services have ceased function. In 2022, the number of individuals treated with ECT per 100,000 population was 1.86, whereas the number of procedures performed per 100,000 people was 6.55. Conclusions Although 2 new public ECT services have been identified, 4 have turned inactive. Most services are linked to public universities, and inactive service points to financial issues as the main factor in service interruption. Brazil has one of the lowest rates of individuals treated with ECT per 100,000 population compared with countries in North America and Europe. Thus, it is essential to raise awareness to improve ECT adoption rates and bring it out of the shadows in Brazil.